Influence Of Sharia Audit And Corporate Goodgovernanceon The Quality Of Financial Reports Of Islamic Commercial Banks In Indonesia For The Period 2020 – 2024 - Sil Sila Rahmayani; Faturrahman; Marissa Putriana (Cita konsultindo, 2026)
The rapid development of the Islamic banking industry demands the availability of quality, transparent, and sharia-compliant financial reports. The quality of financial reports can be influenced by the effectiveness of sharia audits and the implementation of Good Corporate Governance (GCG). This study aims to analyze the effect of sharia audits and Good Corporate Governance (GCG) on the quality of financial reports at Islamic Commercial Banks in Indonesia for the period 2020–2024. This study uses a quantitative method with secondary data obtained from the annual reports of Islamic Commercial Banks and publications of the Financial Services Authority (OJK). The study population consists of all Islamic Commercial Banks in Indonesia, with a sampling technique using Purposive Sampling, based on the sampling technique obtained 12 Islamic Commercial Banks with a total of 60 observations. Data analysis was performed using panel data regression with the help of the EViews 14 program. The results of the study indicate that sharia audits have a positive and significant effect on the quality of financial reports, Good Corporate Governance (GCG) has a positive and significant effect on the quality of financial reports, and sharia audits and GCG simultaneously have a positive and significant effect on the quality of financial reports. Thus, increasing the effectiveness of sharia audits and implementing good GCG can improve the quality of financial reports of Islamic Commercial Banks in Indonesia.